Translational regulation mediated by upstream open reading frames im PERK mRNA - Fernandes, Rafael (2019)
Genome-wide studies pointed out translation as a major regulator of gene expression, being a key post-transcriptional mechanism by which cells rapidly change their gene expression pattern in response to diverse stimuli. Upstream open reading frames (uORFs) are examples of cis-acting elements that can regulate translation initiation. A uORF is defined as a coding sequence located within the 5’untranslated region (5’UTR) of an mRNA and is typically considered a repressor of main ORF (mORF) translation. This can be due to the recognition of the uORF start codon by the preinitiation complex. In this case, when the translating ribosome encounters the uORF stop codon, the translation machinery disassembles, avoiding mORF translation if the ribosome cannot reinitiate at the main start codon. ATF4, CHOP and GADD34 are stress-response proteins encoded by uORF-harboring transcripts with translation repression activity, which is responsible for maintaining a low expression of these proteins in normal conditions. However, when ER stress occurs, the unfolded protein response (UPR) is activated and eIF2α is phosphorylated by PERK. In these cases, the availability of the preinitiation complex is reduced, favoring translation of the mORFs. The stress-response proteins are therefore up regulated, triggering a cascade of events aiming stress resolution and cell survival. In this work we intended to determine if PERK is regulated at the translational level in normal and ER stress conditions. We have validated the annotated sequence of PERK 5’UTR using 5’RACE, and we have selected uORFs based on ribosome profiling data already available. Then, we have cloned the 5’UTR into a reporter plasmid, in frame with firefly luciferase ORF. Using site-directed mutagenesis, we have made constructs with mutated uORFs to evaluate their impact in translation efficiency. Our data suggest that the uORFs have a repressive effect in mORF translation, and we are now dissecting the mechanisms that drive this regulation.